Parkinson's Disease Oral Health Module: Interprofessional Coordination of Care - Cameron B. Jeter; Natalia S. Rozas; June M. Sadowsky; Deborah J. Jones (Association of American Medical Colleges, 2018)
Introduction Patients with Parkinson's disease (PD) suffer progressive neurodegeneration and experience motor and nonmotor symptoms. Oropharyngeal dysfunctions are increasingly recognized as nonmotor PD symptoms that negatively impact a patient's quality of life. This module was primarily created to update dental health professionals and educate dental students on the oral health needs of patients with PD, with an emphasis on interprofessional collaboration and evidence-based dentistry. The module may also benefit other health professionals from different disciplines working with patients with PD. Methods The module was developed to be delivered in one 55-minute large-group session followed by a short assessment and case study discussion. Associated materials include PowerPoint slides with transcript, a narrated video version of the PowerPoint lecture, a quiz, and the case study. Thirty-four first-year dental students were invited to watch the narrated presentation, complete a pre-/postsurvey, and take the quiz. Results All participants agreed dental schools should provide education regarding oral health in patients with neurological disorders, as only 29% of them had previously taken a related class. After watching the presentation, students reported that most of the information was new content and that the difficulty level met their expectations. All students reported that the lecture increased their interest in interprofessional collaboration. In a quiz taken immediately after the presentation, the class average grade was 82.7, with 94% of the class passing the quiz with a grade of 70 or more. Discussion Educating dental professionals regarding care of patients with PD must emphasize interprofessional collaborations among health care providers.